Incidence of sleep apnea in patients with various types of glycemic disturbances - Alexander Vasil'evich Dreval'; Inna Vladimirovna Misnikova; V A Gubkina; M V Agal'tsov; S I Fedorova (Сахарный диабет)
Aims. To assess the risk for sleep apnea in patients with various types of glycemic disorders by means of Epworth Sleepiness Scale andSleep Apnea Screening Questionnaire. Materials and Methods. We examined 744 residents of Mozhaisk Region, that were considered to have high risk for development of type2 diabetes mellitus (T2DM), as estimated by FINDRISK Questionnaire. Patients, who scored 12+ were cleared for participation in this study. Combined score from Epworth Sleepiness Scale and Sleep Apnea Screening Questionnaire was applied for diagnosis of sleep apnea, supplemented with specific questions about snoring and episodes of apnea. Glycemic disorders were diagnosed with standard glucose tolerance test. Results. 42.7% of examined patients (n=318) were diagnosed with various types of glucose disorders. Prevalence of abdominal obe- sity (according to waist circumference measurement) comprised 59.3% in male patients and 54.1% in females. We observed positive correlation between body mass index (BMI) and snoring ? 0.3 (p=0.0001), BMI and apnea ? 0.2 (p=0.0001), BMI and daytime sleepiness ? 0.1 (p=0.007); we also observed direct correlation between age and snoring ? 0.2 (p=0.0001), as well as age and sleep apnea ? 0.1 (p=0.028). Risk for sleep apnea was found to be 4.7 times higher in patients with arterial hypertension. After adjustment71Диагностика, контроль и лечениеСахарный диабет. 2013;(1):71?77Сахар ный диабетfor age risk of apnea remained 2.8 times higher in patients with T2DM, 1.9 times higher in subjects with impaired glucose tolerance and1.6 times higher in subjects with impaired fasting glycaemia. Relative risk for snoring in patients with various types of glycemic disorders was 1.1-1.2 against normoglycemic controls. We estimated that all types of glycemic disorders increase risk for apnea 1.2?1.6 times. Conclusion. Glycemic disorders, body weight excess, obesity and arterial hypertension are risk factors for snoring and sleep apnea. Corresponding patient categories should be screened for sleep apnea by questionnaire survey to identify those in need of further complex examination and treatment.